Attitude Towards The Filipino Language And Communicative Competence Of Senior High School Students In Samar National School (Texas Journal of Philology, Culture and History, 2024)
Enhancing communicative competence in the Filipino language classroom is an ongoing endeavor that demands comprehensive understanding and strategic intervention. The recent study conducted at Samar National School (SNS) delved deep into the attitudes and proficiency levels of Senior High School (SHS) students, revealing a multifaceted landscape characterized by both promising strengths and notable areas for improvement. Within this dynamic context, the study uncovered a prevailing positive attitude towards the Filipino language among student-respondents, signaling a fertile ground for linguistic development and cultural engagement. However, compared against this optimism were evident deficiencies in grammatical and linguistic competence, highlighting a pressing need for targeted interventions to fortify foundational language skills. Amidst these challenges, the study also unveiled strengths in discourse and strategic competence, suggesting a nuanced proficiency profile within the student cohort. The correlation identified between students' attitudes towards the Filipino language and their grammatical competence underscores the intricate interplay between affective factors and linguistic proficiency, emphasizing the importance of cultivating a positive disposition towards language learning. The study advocates for the implementation of evidence-based intervention plans that address identified deficiencies while leveraging existing strengths, thereby fostering a more holistic approach to language education that empowers students to navigate effectively in the Filipino language, enriching their educational journey and cultural identity in the process.